Proceedings of the 2nd International Workshop on Conducting Empirical Studies in Industry 2014
DOI: 10.1145/2593690.2593691
|View full text |Cite
|
Sign up to set email alerts
|

Topic selection in industry experiments

Abstract: This paper shares our experience with initial negotiation and topic elicitation process for conducting industry experiments in six software development organizations in Finland. The process involved interaction with company representatives in the form of both multiple group discussions and separate face-to-face meetings. Fitness criteria developed by researchers were applied to the list of generated topics to decide on a common topic. The challenges we faced include diversity of proposed topics, communication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…Furthermore, the differences in objectives [56,55,51] (C22), reward systems [46,23,48] (C25), and what is perceived as useful (C23) hinder to establish collaborations. For example, Glass and Hunt [57] point out that only few researchers would be interested in doing the development ("D") of R&D. With regard to rewards, it was pointed out that academia does not value industry impact and that there is no academic reward for industry collaborations and success [58,45].…”
Section: Problem Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the differences in objectives [56,55,51] (C22), reward systems [46,23,48] (C25), and what is perceived as useful (C23) hinder to establish collaborations. For example, Glass and Hunt [57] point out that only few researchers would be interested in doing the development ("D") of R&D. With regard to rewards, it was pointed out that academia does not value industry impact and that there is no academic reward for industry collaborations and success [58,45].…”
Section: Problem Formulationmentioning
confidence: 99%
“…'Proper' topic selection (BP19) is of importance early in the process [56,23] and topics need to be prioritized [51]. To choose a topic of interest, the problems of the companies have to be well understood.…”
Section: Problem Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Causevic et al (2010) also conducted an industrial survey to examine the expected and actual level of usage for a number of test-related activities and found that "respondents would like to use TDD to a significantly higher extent than they actually do" due to TDD's claimed benefits in the literature. Our face-to-face meetings with professionals from six software companies in Finland, as part of our on-going project (Juristo 2016), also revealed that TDD is a highly popular topic, as professionals are interested in learning its key practices and its impact on their development process through experimentation (Tosun-Misirli et al 2014).…”
Section: Introductionmentioning
confidence: 92%
“…[27]) and controlled experiments in academic settings (e.g. [18]), the industrial adoption of TDD has not been completed yet [29]. Causevic et al [10], in their literature review, highlighted 18 factors that could limit the industrial adoption of TDD.…”
Section: Introductionmentioning
confidence: 99%